Delivering Positive Newborn Screening Results: Cost Analysis of Existing Practice versus Innovative, Co-Designed Strategies from the ReSPoND Study - Francesco Fusco; Jane Chudleigh; Pru Holder; James R. Bonham; Kevin W. Southern; Alan Simpson; Louise Moody; Ellinor K. Olander; Holly Chinnery; Stephen Morris (MDPI AG, 2022)
Although the communication pathways of Newborn Bloodspot Screening (NBS) are a delicate task, these pathways vary across different conditions and are often not evidence-based. The ReSPoND interventions were co-designed by healthcare professionals alongside parents who had received a positive NBS result for their child. To calculate the cost of these co-designed strategies and the existing communication pathways, we interviewed 71 members of the clinical and laboratory staff of the 13 English NBS laboratories in the English National Health Service. Therefore, a scenario analysis was used to compare the cost of the existing communication pathways to the co-designed strategies delivered by (i) home-visits and (ii) telecommunications. On average, the existing communication pathway cost £447.08 per infant (range: £237.12 to £628.51) or £234,872.75 (£3635.99 to £1,932,986.23) nationally. Implementing the new interventions relying on home-visits exclusively would cost on average £521.62 (£312.84 to £646.39) per infant and £297,816.03 (£4506.37 to £2,550,284.64) nationally, or £447.19 (£235.79 to £552.03) and £231,342.40 (£3923.7 to £1,922,192.22) if implemented via teleconsultations, respectively. The new strategies delivered are not likely to require additional resources compared with current practice. Further research is needed to investigate whether this investment represents good value for money for the NHS budget.